Pemanfaatan Cerita Rakyat Berbasis Antroekologi Sastra dalam Pembelajaran di Sekolah Menengah Atas: Menanamkan Nilai-nilai Budaya dan Lingkungan - Nadhira, Yulia; Tanjung, Rezki Agus Pandai Yani; Suherlinda, Suherlinda; Hutagalung, Santa Hoky; Harahap, Muharrina; Wuriyani, Elly Prihasti (Jurnal Bahastra, 2025)
This study examines the use of folklore based on literary anthroecology in high school learning as a means to instill cultural values and environmental awareness among students. Literature serves not only as a source of reading but also as a medium to understand the interrelationship between humans, nature, and culture. Folklore from North Sumatra, such as the legends of Lake Toba, Sampuraga, and Batu Gantung, is closely connected to ecological aspects and local wisdom that can be applied in literature-based anthroecological learning. Employing a library research method with a descriptive approach, this study analyzes the interconnections between literature, culture, and ecology within folklore. The findings reveal that folklore holds not only aesthetic literary value but also reflects human interaction with nature while embodying social and cultural values that enrich students’ perspectives. Literature learning through an anthroecological approach can be implemented through critical discussions, contextual analyses, and ecology-based literacy projects. Nevertheless, challenges remain, particularly teachers’ limited capacity to apply anthroecological methods and the scarcity of appropriate learning resources. Hence, effective strategies such as the development of teaching modules, teacher training, and the integration of technology are required to optimize the implementation of this approach in high school literature education.